Исследования в области нанотехнологий в провинциальном техническом вузе: иллюзии и реальность - Мурзин, Л.М. (Вісник Українського матеріалознавчого товариства, 2016)
The discussion material about feasibility and possibility of the experimental researches in the field of complex high-tech areas as part of the educational program of specialist training technologies in the technical institute of highest education, which has limited financial capabilities of the equipment of laboratory facilities relevant subjects of the complex and expensive research equipment has been presented in this paper.